2014
DOI: 10.1111/febs.12841
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of diacylglycerol acyltransferase 2 protein stability by gp78‐associated endoplasmic‐reticulum‐associated degradation

Abstract: Triacylglycerol (TG) is the major form of stored energy in eukaryotic organisms and is synthesized by diacylglycerol acyltransferase (DGAT) in the endoplasmic reticulum (ER). DGAT2, one of the two DGAT enzymes, is barely detectable in cells, even though its mRNA transcripts are maintained at considerable levels. However, little is known about how DGAT2 expression is altered by protein stability. DGAT2 was highly unstable in cells and was rapidly degraded by proteasomes in an ubiquitin-dependent manner. Deletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…Additionally, DGAT2 has multiple potential phosphorylation sites (Yen et al, 2008), suggesting post-translational regulation of its stability or activity. DGAT2 is a short-lived protein (T 1/2 of ~ 30 min) that is degraded by ER-associated protein degradation (Brandt et al, 2016; Choi et al, 2014). Therefore, fast turnover of DGAT2 could also enable efficient down-regulation of its activity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, DGAT2 has multiple potential phosphorylation sites (Yen et al, 2008), suggesting post-translational regulation of its stability or activity. DGAT2 is a short-lived protein (T 1/2 of ~ 30 min) that is degraded by ER-associated protein degradation (Brandt et al, 2016; Choi et al, 2014). Therefore, fast turnover of DGAT2 could also enable efficient down-regulation of its activity.…”
Section: Discussionmentioning
confidence: 99%
“…Many LD proteins are strongly stabilized in cells treated with oleate, suggesting that their stability is increased by insertion into LDs. In addition, degradation of some Class I LD proteins in the ER results in their relative enrichment on LDs [106,107]. …”
Section: Establishing the Ld Proteomementioning
confidence: 99%
“…An additional mechanism for regulating early steps in LD formation could be the stabilization of machinery necessary for LD growth and budding at predetermined sites. This idea is supported by a study in mammalian cells which demonstrated that overexpressed Class I LD protein DGAT2, a TAG-synthesis enzyme that functions in LD expansion, is degraded through an ERAD pathway that uses the E3 ligase gp78 [107]. These findings support the hypothesis that degradation of LD proteins by ERAD is a mechanism that maintains the composition of the ER proteome, contributes to the relative enrichment of ER proteins at LDs or sites of LD biogenesis, and degrades LD proteins during lipolysis.…”
Section: Connections Between Lds and The Ubiquitin-proteasome Systemmentioning
confidence: 99%
“…On LDs, DGAT2 cooperates with other TAG synthesis enzymes and contributes to local TAG synthesis and LD growth (194). A recent study demonstrated that DGAT2 (Figure 3), but not DGAT1, is rapidly degraded in cultured HEK293T cells and accumulates in a ubiquitinated form following proteasome inhibition (17). Depletion of the E3 ligase gp78, but not MARCH6, FBXW7, or Hrd1, stabilized DGAT2 and reduced DGAT2 ubiquitination (17).…”
Section: Erad Regulation Of Triacylglycerol Metabolismmentioning
confidence: 99%